Enhancing Vocational Identity and Practical Skills Motivation through Vocational Mentoring Intervention: A Quasi-Experimental Study on Automobile Students - Ogbuanya, Chinyere Theresa (International Journal of Research in Counseling and Education, 2023)
This quasi-experimental study investigates the impact of vocational mentoring intervention on vocational identity (exploration - in-breadth and in-depth, commitment, reconsideration), as well as practical skills motivational beliefs and engagement among Automobile students. The research, testing five hypotheses, utilized a sample of 137 students, with 81 in the intervention group and 56 in the control group. Data collection employed a questionnaire and rating scale with high overall reliability coefficients of 0.86 and 0.84, respectively. The intervention, structured as a two-phase plan, was designed to enhance vocational identity and practical skills motivation. Analysis of covariance (ANCOVA) and Multivariate Analysis of Covariance (MANCOVA) were employed for data analysis. The findings indicated a significant positive effect of the intervention on vocational identity, leading to progressive improvements in exploration, commitment, and reconsideration. Additionally, the study observed progressive increases in practical skills' motivational beliefs and engagement. The study recommends the implementation of periodic vocational mentoring in technical colleges to nurture students' vocational identity and enhance their practical skills motivational beliefs and engagement.